Marketing experiencial y fidelización de clientes de la avícola Don Pollo de Iquitos 2024 - Young Gonzales, Jose Ricardo (2025)
The purpose of this research was to determine the impact of experiential marketing on customer loyalty at the Don Pollo poultry farm in Iquitos 2024. We opted for a basic study, with a quantitative, correlational approach and a non-experimental, cross-sectional sampling design. The sample consisted of 100 customers, for the survey conducted by a questionnaire for data collection. The findings show that between the variables Experiential Marketing and Customer Loyalty there is a positive impact, with a significance value of p=0.000. Likewise, the dimension loyalty as behavior, presents a significance value of p=0.000; likewise, the dimension attitudinal loyalty, shows a significance value of p=0.000; also, the cognitive loyalty dimension, shows a significance value of p=0.000; which indicates that the variable Experiential Marketing has a positive impact with these dimensions.